2012
DOI: 10.1166/jnn.2012.5177
|View full text |Cite
|
Sign up to set email alerts
|

Controllable Synthesis of ZnO with Various Morphologies by Hydrothermal Method

Abstract: ZnO microstructures with various morphologies have been controllably synthesized by hydrothermal route using different precipitant and zinc source in liquid solution. X-ray diffraction (XRD) and scanning electron microscopy (SEM) were used to characterize the ZnO2, Zn(OH)2 and ZnO structures to understand the role of precipitant and precursors in the growth of various morphologies. The nucleation and growth process can regulate by changing the precipitant. When H2O2 was used as precipitant, ZnO particles with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 29 publications
0
9
0
Order By: Relevance
“…Nanocrystalline ZnO exhibits variety of morphological structures like nanorods, nanowires, nanoribbon, nanoflower, nanowalls, quantum dots, nanopyramids, etc. [3][4][5][6][7][8]. It exhibits a prolific combination of multifunctional properties especially structural, thermal, semiconducting, optoelectronic, optical and piezoelectric properties.…”
Section: Introductionmentioning
confidence: 99%
“…Nanocrystalline ZnO exhibits variety of morphological structures like nanorods, nanowires, nanoribbon, nanoflower, nanowalls, quantum dots, nanopyramids, etc. [3][4][5][6][7][8]. It exhibits a prolific combination of multifunctional properties especially structural, thermal, semiconducting, optoelectronic, optical and piezoelectric properties.…”
Section: Introductionmentioning
confidence: 99%
“…[17][18][19][20] Typically, 5 mmol FeCl 3 · 6H 2 O was dissolved in EG (50 mL) to form a stable orange solution, then 50 mmol NH 4 Ac and appropriate amount of the surfactant (R) were added respectively into the above solution under vigorous magnetic stirring until completely dissolved. The mixture was transferred to a Teflon-lined stainless-steel autoclave (50 mL) and sealed to heat at 200 C for 12 h, followed by cooling to room temperature naturally.…”
Section: Preparation Of Fe 3 O 4 @Sio 2 Nanoparticlesmentioning
confidence: 99%
“…[10][11][12] In the synthesis process of MSNs by the modified Stöber method, 13 a new type of spiral mesoporous silica nanorods (MSNRs) with different aspect ratios was synthesized by adjusting the dosage of NH 3 ⋅H 2 O. 14,15 Interestingly, a recent study reported that the "rotational hopping" movement of nanorod particles can promote its diffusion speed in the grid like mucin fluid; therefore, nanorods can effectively improve the efficiency of drug delivery. 16 The MSNRs fabricated by our method possessed the characteristics of large pore volume and specific surface area, and had the potential as a new drug carrier.…”
Section: Introductionmentioning
confidence: 99%